2001
DOI: 10.1038/sj.bjp.0703915
|View full text |Cite
|
Sign up to set email alerts
|

The role of several α1‐ and α2‐adrenoceptor subtypes mediating vasoconstriction in the canine external carotid circulation

Abstract: 1 It has recently been shown that both a 1 -and a 2 -adrenoceptors mediate vasoconstriction in the canine external carotid circulation. The present study set out to identify the speci®c subtypes (a 1A , a 1B and a 1D as well as a 2A , a 2B and a 2C ) mediating the above response. 2 Consecutive 1 min intracarotid infusions of phenylephrine (a 1 -adrenoceptor agonist) and BHT933 (a 2 -adrenoceptor agonist) produced dose-dependent decreases in external carotid blood ow, without aecting mean arterial blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 29 publications
2
29
1
1
Order By: Relevance
“…Abound et al (1993) showed that the administration of 5-methylurapidil, benoxanthian, and WB 4101 to the incubation chamber decreased the aorta contraction strength in rats in response to noradrenaline. Blockade of the α 1B -adrenergic receptor by addition of L-765.314 did not have any influence on tissue reaction to phenylephrine (Willems et al 2001) which is not in agreement with our results. The role of α 1B -adrenergic receptor in arteries vasoconstriction in dogs seems controversial.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Abound et al (1993) showed that the administration of 5-methylurapidil, benoxanthian, and WB 4101 to the incubation chamber decreased the aorta contraction strength in rats in response to noradrenaline. Blockade of the α 1B -adrenergic receptor by addition of L-765.314 did not have any influence on tissue reaction to phenylephrine (Willems et al 2001) which is not in agreement with our results. The role of α 1B -adrenergic receptor in arteries vasoconstriction in dogs seems controversial.…”
Section: Discussioncontrasting
confidence: 51%
“…In vivo studies showed that stimulation of the α 1 -adrenergic receptor by intravenous phenylephrine caused constriction of the arterial vessels in pigs and dogs (Willems et al 2001). The researchers showed a significant increase in the muscle tonus of the arterial vessels, leading to an increased arterial blood pressure of the examined animals.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Studies on these models showed that the canine carotid vascular responses to the α 2 -adrenoceptor agonist BHT933 were markedly attenuated by the α 2A -adrenoceptor antagonist BRL44408 or the α 2C -adrenoceptor antagonist MK912 (given either alone or in combination) but remained unaffected after administration of the α 2B -adrenoceptor antagonist imiloxan. Figure 3 (right panel) illustrates the effect of α 2 -adrenoceptor subtypes in the canine carotid vascular bed (Willems et al 2001a). Similarly, the carotid vasoconstrictor responses produced by BHT933 in anesthetized pigs were markedly attenuated by MK912, while the other antagonists were ineffective .…”
Section: Adrenoceptorsmentioning
confidence: 94%